Genetic Susceptibility to Epithelial Ovarian and Endometrial Cancer - Kankuri-Tammilehto Minna (JSciMedCentral, 2025)
Multigene next generation sequencing (NGS) panel technology, massive parallel sequencing, can efficiently and economically analyze genes in 3 to 6 weeks. There are agreed criteria based on which to suspect hereditary ovarian and endometrial cancer and thus to make a referral to clinical genetic unit.
The geneticist interprets the genetic results and the information from pedigree. When a person is diagnosed with pathogenic variant (mutation) with genetic susceptibility to ovarian and endometrial cancer, counseling is provided on the associated cancer risk and appropriate monitoring is organized. Healthy family members with mutation can participate in recommended surveillance. Identifying carriers allows treatment and follow-up to reduce the morbidity and mortality for cancer patients and their healthy relatives.
This is a case report on gene test results in hereditary breast and ovarian cancer syndrome (HBOC) families who have ovarian cancer in southwestern Finland. And a review of genetic susceptibility to ovarian and endometrial cancer.